Technology cloud computing strategy At PT. Synnex Metrodata Indonesia - Imbang Agung Gumilang Yulius, Muhammad; Aldianto, Leo (The Indonesian Journal of Business Administration, 2016)
Abstract - This study describes the strategy of PT. SMI in the era of cloud technology. During this time PT. SMI only focus with the sale of software and hardware only and have not been exploring the world of cloud different with competitors who have previously in cloud business. Sales cloud continues to grow rapidly in Indonesia and PT. SMI should immediately adjust role in the field of this cloud and already many users it uses this cloud services. In addressing these problems, there are several alternatives that can be used by PT. SMI. Alternative is in the improvements of internal sector so that PT. SMI also not lagging behind again in the business of it. Second improvement is in the resource sector in order to have quality resources. Third improvements is in the planning sector to match what will be achieved. Fourth is in the sector processes that must be run properly and the last is from the sector of the product to be chosen later that will be marketed by PT.SMI. From the analysis of the alternatives was generate cloud solution to, that is by providing technology training in the present and the future on a regular basis so that PT. SMI is ready to face the new world of cloud technology. Then do research on a new technology and its possibilities can develop the technology in Indonesia. Creating standardized procedures for activities and create a new department that is focused on new technologies. The solution to business also is doing the selection target user segment in the small business sector first, and then make the selection cloud product which will be marketed with a focus first on the infrastructure sector. With such a solution has clear what will be done and the implementation will divided into two time periods as for a period of 3 months during the first and the second time is for 12 months. Keywords: cloud, cloud strategy, business clouds